قياس القدرة الانتمائية في منظمات الاعمال في الاردن - د. سرمد كوكب الجميل; احمد محمد حسن نور (PROSPECTIVE RESEARCHES, 2023)
The present study is an attempt to analyze and measure the credit worthiness of business organizations in Jordan. It has included industry and banking sectors of registered companies in Amman Market Stock Exchange. Many significant variables have been identified for the measurement of credit worthiness for the banks and companies by using numbers of financial ratios, viz. profitability and liquidity ratios. The study has covered the period (2000-2002) which is suitable for the purposes of the current study. Factor analysis has been used to shortcut the special variables of credit ratios for this purpose. Such variables represent the second aspect of the credit worthiness of banks and this is done by using cross sectional regression models, and pooled regression model to test the research hypotheses. The study has concluded the necessity of improving the risks management, achieving balance between risk and return, and reducing credit risk due to late loans and abstain from performing of borrowers.